2021
DOI: 10.3390/bs11110149
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Stressful Life Experiences Scale and the Inventory of Complicated Spiritual Grief: The Italian Validation of Two Instruments for Meaning-Focused Assessments of Bereavement

Abstract: Background: Bereavement is an inevitable event that can cause pain, discomfort, and negative consequences in daily life. Spirituality and religiosity can help people cope with loss and bereavement. Sometimes, however, the death of a loved one can challenge core religious beliefs and faith, which has been found to be a risk factor for prolonged mourning. Objectives: (1) Determine whether the Italian versions of the Integration of Stressful Life Experiences Scale (ISLES) and Inventory of Complicated Spiritual Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…This approach helps to recognize meaningful experiences and live with grieving experiences, cherishing the memories [ 44 ]. The meaning-focused coping and intervention were found advantageous in the time of the COVID-19 outbreak [ 45 , 46 , 47 ]…”
Section: Discussionmentioning
confidence: 99%
“…This approach helps to recognize meaningful experiences and live with grieving experiences, cherishing the memories [ 44 ]. The meaning-focused coping and intervention were found advantageous in the time of the COVID-19 outbreak [ 45 , 46 , 47 ]…”
Section: Discussionmentioning
confidence: 99%
“…The authors identified a two-factor structure of (a) "Insecurity toward God" and (b) "Disruption in religious practice." The Cronbach's alpha of the original total scale is 0.96 [37]. Sample items are: "I no longer feel safe and secure from God"; "I don't feel much desire to join the community to praise God or glorify him" [47].…”
Section: Instrumentsmentioning
confidence: 99%
“…However, Burke and Neimeyer (2013) [36] found that the death of a loved one can also trigger a spiritual struggle. Neimeyer and colleagues (2021) [37] found that survivors of violent and traumatic loss may exhibit negative religious coping and depression. Higher levels of depression were associated with increased spiritual struggle, particularly in cases where the relationship with God was perceived as lost or damaged.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical research in recent years has reflected increasing interest in the topic of loss, grief and bereavement, focusing particularly on resilience and coping factors. The article “The Integration of Stressful Life Experiences Scale and the Inventory of Complicated Spiritual Grief: The Italian Validation of Two Instruments for Meaning-Focused Assessments of Bereavement” [ 11 ] discusses an original aspect of loss and grief: the religious crisis, as caused by trauma or the death of a loved one. Another innovative area of study is that of coping with grief through the internet.…”
Section: On Loss Bereavement and The Covid-19 Pandemic Crisismentioning
confidence: 99%